Pengaruh Kualitas Produk Dan Kepercayaan Terhadap Loyalitas Konsumen Dengan Kepuasan Konsumen Sebagai Variabel Intervening : Studi Pada Pelanggan Mie Ayam Abah Di Kecamatan Sei Rampah - Sinurat, Yenni; Arnanda, Anjani (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2023)
This study aims to determine how the influence of product quality and trust on consumer loyalty with consumer satisfaction as an intervening variable (Study on Abah Chicken Noodle Customers in Sei Rampah District). The population in this study were all consumers of Mie Ayam Abah. In determining the sample used the Slovin formula with Accidental Sampling sampling technique, the sample taken was 97 respondents. The analysis tool in this study uses the help of the Smart PLS software version 3.0. The results showed that: 1). Product Quality variable has a positive and significant effect on Consumer Satisfaction, 2). Trust variable has a positive and significant effect on Consumer Satisfaction, 3). Product Quality variable does not have a significant positive effect on Consumer Loyalty, 4). Trust variable has a positive and significant effect on Consumer Loyalty, 5). Consumer Satisfaction variable has no positive effect on Consumer Loyalty, 6). Product Quality variable does not have a positive effect on Consumer Loyalty with Consumer Satisfaction as an Intervening variable, 7). Trust variable has no effect on Consumer Loyalty with Consumer Satisfaction as the Intervening variable.